Are older workers worthy of their pay? An empirical investigation of age-productivity and age-wage nexuses - Ana Rute Cardoso; Paulo Guimar\~aes; José Varej\~ao (Institute for the Study of Labor (IZA), 2010)
Using longitudinal employer-employee data spanning over a 22-year period, we compare age-wage and age-productivity profiles and find that productivity increases until the age range of 50-54, whereas wages peak around the age 40-44. At younger ages, wages increase in line with productivity gains but as prime-age approaches, wage increases lag behind productivity gains. As a result, older workers are, in fact, worthy of their pay, in the sense that their contribution to firm-level productivity exceeds their contribution to the wage bill. On the methodological side, we note that failure to account for the endogenous nature of the regressors in the estimation of the wage and productivity equations biases the results towards a pattern consistent with underpayment followed by overpayment type of policies.
Keywords: J14; J24; J31; 330; aging; productivity; wages